Analisis Kelayakan Usaha Akomodasi : Studi Kasus Sriwijaya 8 Kost - Gabriela Hendratno; Marchellino Fergie Sanjaya; Velicya Tarisha Cheung; Willie Natanael; Budi Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Sriwijaya 8 Kost is an accommodation business located in Curug Sangereng, Gading Serpong. This business was developed to meet the housing needs of students and workers in the area. This study aims to analyze the feasibility of Sriwijaya 8 Kost based on nine aspects, namely legal aspects, human resource management aspects, market and marketing aspects, technical aspects, consumer behavior aspects, financial aspects, PEST aspects, environmental & industrial aspects, and risk aspects. This study uses a qualitative approach with a case study method through observation, interviews, and document analysis. The results show that the business has great market potential, supported by its strategic location and appropriate consumer segmentation. Technical planning related to facilities, layout, and operations has been well designed to ensure the comfort and safety of residents. Financial analysis shows that the business is feasible with a BEP of 3 rooms per month, a payback period of 7.7 years, an IRR of 5.023%, and an ROI of 129.5%. External factors such as government policies and high demand for housing further strengthen the feasibility of the business. Overall, Sriwijaya 8 Kost is deemed viable for operation and development, with a need for continuous improvement in legality, financial record-keeping, service quality, and risk mitigation.